বাংলাদেশের মক্তিযুদ্ধ, পত্রিকাপঞ্জি - আজাদ, কুতুব 1973-; মন্তাজ, সাহেদ 1973-
Index to articles on the liberation war of Bangladesh as reflected in 1971, in contemporary English newspapers published from various countries of the world.